Misuse of Over the Counter and Prescription Only Medication by Adults Accessing Specialist Treatment Services in the UK: A Narrative Synthesis - Rosalind Gittins; Louise Missen; Ian Maidment (SAGE Publishing, 2022)
Background: Concerns about the misuse of over the counter (OTC) and prescription only medication (POM) are due to their impact upon physical/mental wellbeing, drug interactions and drug-related deaths. Improving an understanding of the pattern of use by people accessing specialist substance misuse services (SMSs) should enable improvements to treatment provision. Aim: To review the literature on the misuse of OTC/POM among adults accessing SMS, including the pattern of use, types of medication and associated characteristics. Methods: This review is reported in line with PRISMA. The protocol has been registered on PROSPERO (CRD42020135216) and separately published. A search of Cochrane, OVID Medline, Pubmed, Scopus and Web of Science databases and grey literature was undertaken. Only English language publications outlining OTC/POM misuse by adults in receipt of psychological/pharmacological interventions for substance misuse were included. Two reviewers conducted the title, abstract and full-text reviews using predetermined selection criteria and a piloted data extraction form to ensure a consistent approach. A third reviewer resolved disagreements and the Mixed Methods Appraisal Tool assessed for bias. Ethical approval was not required. Results: Thirteen studies with notable heterogeneity were included in the narrative synthesis after non-UK-based and ineligible publications were excluded, from the 143 potentially relevant papers. To reduce bias all studies were included in the analysis and GRADE-CERQual was applied. 'High confidence' was identified for all review findings, despite moderate methodological limitations. Antihistamine, benzodiazepine and opioid misuse was mentioned most frequently. Usage patterns and supply sources varied. Adverse consequences and polypharmacy are concerning. Withdrawal symptoms perpetuated misuse, often alongside illicit substance use, comorbid psychiatric/pain disorders and street drug shortages. Conclusion: OTC/POM misuse is common amongst adults accessing SMS. A renewed approach to withdrawal management is required. The limited number of studies may impact on generalisability but allowed for a more detailed review. Restricting to UK studies improved relevance due to drug market variations and availability of medicines in different countries. Further UK-based research on OTC/POM misuse in SMS is needed to build upon the current paucity in the published literature.